Destructive Effect of Calcium Hypochlorite against Pseudomonas aeruginosa Biofilm - Ilma Arifani; Gita Widya Pradini; Insi Farisa Desy Arya; Adi Imam Cahyadi (Althea Medical Journal, 2017)
Background: Pseudomonas aeruginosa is the most common bacteria contaminating the hemodialysis water and has high capability to form a biofilm. The presence of biofilm is hazardous because it becomes a constant source of bacterial and toxin release toward the hemodialysis patient’s blood. Calcium hypochlorite (Ca(OCl)2) is an easily obtained disinfectant. This study was aimed to detect the destructive effect of Ca(OCl)2 against P. aeruginosa biofilm and the optimal disinfectant concentration required to achieve significant effect.Methods: This experimental study was conducted in six replicates from September to October 2015 in Microbiology Laboratory of Faculty of Medicine Universitas Padjadjaran Bandung. A modified tissue culture plate method was performed to grow P. aeruginosa biofilms which were subsequently treated with Ca(OCl)2 in various chlorine concentrations, namely 20, 30, 40, and 500 parts per million (ppm). The data was analyzed using Welch Analysis of Variance (ANOVA) and Games-Howell post-hoc tests and presented in tables.Results: Data were obtained from 36 flat-bottomed polystyrene wells. There was a statistically significant mean difference between groups [F(4, 11.92)= 91.198, p<0.001)]. All of the tested chlorine concentrations caused significant decreases in biofilm optical densities (p = 0.027 for 20 ppm and p< 0.001 for 30, 40, and 500 ppm).Conclusions: Ca(OCl)2 with chlorine concentrations of 20, 30, 40, and 500 ppm have significant destructive effect against P. aeruginosa biofilm. The mean differences among treated groups were not significant. The most optimum concentration is 30 ppm.